2019
DOI: 10.1111/andr.12606
|View full text |Cite
|
Sign up to set email alerts
|

Sperm functional aspects and enriched proteomic pathways of seminal plasma of adult men with obesity

Abstract: BackgroundPrevious studies have demonstrated an association between obesity and the decreased male fertility.Objectiveto observe the mechanisms by which obesity affects semen quality.Materials and methodsA prospective study was performed including 47 male volunteers, of which 27 were obese group (body mass index >30 kg/m2) and 20 were eutrophic (body mass index between 18.5 and 25 kg/m2) controls. Sperm functional analysis was performed. The remaining seminal plasma was pooled—four pools per group— and subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 70 publications
0
31
1
1
Order By: Relevance
“…Positive values indicated that the specific unhealthy BMI category has better seminogram parameters than normal weight, whereas negative ES indicates poorer seminogram parameters. In the case of prospective studies, 32 baseline values were used. In most of the cases, these values were directly obtained from the main data of the article (or supplemental data), and in few cases, the values were obtained through a request to the corresponding authors.…”
Section: Statistical Analysis (Meta-analysis)mentioning
confidence: 99%
“…Positive values indicated that the specific unhealthy BMI category has better seminogram parameters than normal weight, whereas negative ES indicates poorer seminogram parameters. In the case of prospective studies, 32 baseline values were used. In most of the cases, these values were directly obtained from the main data of the article (or supplemental data), and in few cases, the values were obtained through a request to the corresponding authors.…”
Section: Statistical Analysis (Meta-analysis)mentioning
confidence: 99%
“…As a result, any factors that impact the overall antioxidant status of an individual, and thus the bioavailability of extracellular antioxidants, can have an impact on the levels of oxidative stress suffered by the male germ line and thence fertility ( 180 , 181 ). Examples of such conditions include diet ( 182 ), varicocele ( 183 ) smoking ( 184 ), obesity ( 185 ), heat stress ( 186 ), and environmental toxicants such as bisphenol A ( 187 ) all of which can impact systemic antioxidant tone and thus the vulnerability of spermatozoa to oxidative stress. Inadequate intracellular and extracellular antioxidant protection could therefore be a major factor in the etiology of both male infertility and oxidative DNA damage to the paternal genome ( 188 ).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Proteomics analysis of seminal plasma from obese men revealed 69 proteins differentially expressed, enriched in pathways such as apoptosis, activation of immune and inflammatory responses, and antioxidant activity compared with males with a normal BMI. Simultaneously, sperm in the obesity group presented decreased non-progressive motility and acrosome integrity and increased sperm DNA fragmentation [ 25 ].…”
Section: Protein Compositions Of Spmentioning
confidence: 99%
“…Alterations in distinct pathways can be induced by internal healthy state and external factors. Obesity negatively regulates proteins enriched in the intrinsic pathway of apoptosis, activation of immune and inflammatory responses, and antioxidant activity [ 25 ]. In bilateral varicocele patients, compared with healthy men, pathways involved in response to reactive oxygen species and oxidative stress and tissue homeostasis were affected [ 19 ].…”
Section: Sp Factors and Related Pathwaysmentioning
confidence: 99%